A1.7 Interferon and B-Cell Gene Signatures Contribute to Diagnosis of Pre-Clinical Rheumatoid Arthritis. (25th February 2013) - Lubbers, Joyce; Stadt, Lotte A van de; Vosslamber, Saskia; Wesseling, John G; Oztürk, Senay; Schaardenburg, Dirkjan van; Verweij, Cornelis L
Abstract : Background/Objective: Early diagnosis of the preclinical phase of rheumatoid arthritis (pre-RA) allows timely start of treatment with the potential to prevent disease progression. It is known that antibodies against citrullinated proteins (ACPA) and rheumatoid factor (RF) have diagnostic value to identify pre-RA. However, since only 20–40% of ACPA + /RF + arthralgia patients develop arthritis within 5 years, better prognostic markers are needed. Recently, we demonstrated involvement of interferon (IFN) response and B-cell gene signatures in pre-RA. The objective is to demonstrate the value of these signatures to diagnose pre-RA. Methods: Peripheral blood (Paxgene) was collected from 115 ACPA + /RF + arthralgia patients who were clinically followed for arthritis development, one or more swollen joints, with a mean follow-up time of 23 months (IQR 12–30). An IFN and B-cell score was calculated based on 7 Type I IFN response genes and 3 B-cell related genes, respectively, measured by multiplex qPCR. Cox regression analysis and Receiver Operating Characteristic (ROC)-curve analysis were used to demonstrate prognostic and diagnostic significance. Results: Out of 115 arthralgia patients 44 developed arthritis after a median time of 8 months (IQR 5–13). Stratification of these individuals based on the IFN score revealed that 60% of the IFN high patients converted to arthritis compared to 32% in IFN low patients (P = 0.011). For the B-cell signature, 58% in B-cell low patients developed arthritis, compared to 33% of B-cell high patients (P = 0.020). Combined analysis revealed a significant high risk for arthritis development in IFN high /B-cell low patients (80%, hazard ratio (HR) 6.22, P = 0.003) and a low risk for IFN low /B-cell high patients (26%, HR 0.16, P = 0.003). To demonstrate clinical utility a ROC-curve was constructed of ACPA + /RF + alone and in combination with both signatures. The area under the curve reached 0.619 (P = 0.032, CI 0.514–0.724) for ACPA + /RF + and increased to 0.803 (P = 0.0001, CI 0.718–0.888) with IFN and B-cell signatures included. The sensitivity to diagnose pre-RA increased from 16% to 52% when both signatures are included, with a cut-off of 94% specificity. Conclusions: These findings demonstrate the clinical value of IFN and B-cell gene signatures as biomarkers for the diagnosis of pre-RA. This research was supported by the Center for Translational Molecular Medicine (CTMM) consortium "TRACER".